Landasan Inovasi Pendidikan Kurikulum Islami di Aceh (Landasan Yuridis, Historis, dan Keilmuan) - Junaidi Junaidi; Muhibuddin Muhibuddin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The presence of Islam in the area of the Aceh community has a color that has its own focal point in the development of the socio-cultural history of the Acehnesepeople themselves. In the history of the people of Aceh, that Aceh itself consists of several small kingdoms, such as; Samudra Pasai, Peureulak, Pidie and Daya,with the unity of all the kingdoms of Aceh, then Aceh became a big country. In every business, which consists of activities and actions that are intentional toachieve a goal must have a good and strong foothold. Therefore Islamic education is a forum to form an Islamic human being, in this case certainly has a clear reference / foundation in all aspects in it. On this occasion the author refers to the foundations juridical, history and science